An investigation of the current management of asthma in adolescents and children in Saudi Arabia, barriers to optimal care, and the influence of patient education - Al Thagfan, Sultan Saad (Curtin University, 2012)
The incidence of childhood asthma in the kingdom of Saudi Arabia (KSA) ranges from 4% in some regions to 23% in others. Although international and national guidelines have been issued to improve the management of asthma, their implementation has not been as expected or hoped for. For instance, while the guidelines recommend the use of inhaled corticosteroids (ICS) as the first choice in chronic asthma treatment, international research shows that the use of these agents is suboptimal. This holds true in KSA. Many reasons have been suggested for the lack of implementation of guidelines and the inappropriate use of corticosteroids, including poor patient knowledge, attitudes and education, physician confidence and performance, health care costs, and available facilities.This research consists of four phases investigating the current practice of asthma management among both patients (children and adolescents) and physicians in primary health care in KSA with regard to the Saudi National Protocol for the Management of Asthma; it identifies barriers affecting young and adolescent patients’ and their families’ adherence with asthma management protocols and adherence with ICS use. It also evaluates the effects of education intervention and the provision of asthma action plans (AAPs).The first phase documents current patterns of management of asthma in children and adolescents in KSA, to assess the pattern and appropriateness of corticosteroid use in childhood asthma and to evaluate asthma management practice in primary health care centres (PHCCs) against the national protocol. A total of 230 respondents (56.1% male and 43.9% aged 5 to <10 years), comprising patients (or their carers) from Asser and Riyadh, completed a survey using a translated hybrid of the FACCT quality measures (Adult Asthma Measurement Survey-version 2.0) and Asthma Therapy Assessment Questionnaire (ATAQ) to provide data on patterns of asthma treatment, degree of asthma control, use of AAPs and PFMs (peak flow meters), and levels of patient education and knowledge. The majority of respondents in both regions had asthma classified as either mild or moderately severe (85.7%). Only 34.8% used ICS, while around two thirds (60.6%) used a β2 agonist only. Low adherence with PFM, spacer, and AAP use, and poor patient education, were found; as were regional variations. The conclusion is that asthma management tends to be inconsistent with national guidelines. Poor knowledge, attitudes, behaviours and self-efficacy, as well as lack of communication between patients/ carers and professionals, contribute to unsatisfactory management outcomes. The majority of study subjects did not have well controlled asthma.The second phase investigates physicians’ compliance with the National Protocol Asthma Guidelines in two regions of KSA. A total of 87 physicians from Riyadh (44) and Asser (43) completed a survey of strategies for management of asthma. The majority reported access to The National Protocol for the Management of Asthma at the point of care. Information about medication was provided by 78.2% of physicians to patients with moderate asthma and by 85.1% to those with severe asthma. AAPs were provided by 36.8% of physicians for patients with mild asthma, 55.8% for patients with moderate asthma, and 69.0% for those with severe asthma. Recommendations to use ICSs varied from 16.1% to 88.5% amongst six vignettes reviewed by the physicians. Bronchodilators were commonly recommended, and in some cases oral corticosteroids were deemed inappropriate. Compliance with national guidelines was found to be less than optimal. Poor communication between health care providers and patients/ carers was observed.A third survey uses The Illness Management Survey (IMS) and ICS scales for the purpose of identifying the barriers affecting Saudi asthma patients; it finds that 40% of participants believed that medications were unhelpful and doctors did not involve the patient in decision-making. Fewer than 40% of respondents reported adequate access to information. Low use of AAPs and PFMs, with inappropriate treatment, was observed; and ICS use adherence in this phase was low, with less than one third of respondents reporting daily use of ICSs. A majority reported more than five barriers to adherence with asthma management in general and ICS use especially, including lack of knowledge, patient behaviours and attitudes, lack of self-efficacy, misconceptions, misunderstandings among patients/ carers, poor communication, and lack of motivation and social support.The fourth phase evaluates the impact of an educational intervention and the provision of AAPs on asthma management outcomes. One group of patients was provided with education alone; a second group received education plus an AAP. Both groups A (n = 105) and B (n = 99) completed pre-intervention and post-intervention surveys. Both groups completed three steps: (1) a baseline self-administered questionnaire, (2) an education program, (3) a three-month follow-up period with the re-administration of the baseline questionnaire at the conclusion. Group A patients were also provided with an AAP. The education program improved patients’/ carers’ knowledge, behaviours/ attitudes, and self-efficacy, as well as their ability to communicate with health care providers; and resulted in improved asthma management outcomes. Use of controller medication and adherence increased. Furthermore, patients in the intervention stages had fewer asthma symptoms and better control of their asthma, which resulted in better quality of life. The conclusion is that the education program coupled with the provision of AAPs and follow-up achieved significantly better results.The overall of the study has found a number of differences in asthma management in KSA. In particular, an intervention and provision of AAPs and follow-ups led to notable improvements in patient outcomes.